2003
DOI: 10.1139/p03-025
|View full text |Cite
|
Sign up to set email alerts
|

Rate of decay of specific surface area of snow during isothermal experiments and morphological changes studied by scanning electron microscopy

Abstract: The quantification of the specific surface area (SSA) of snow crystals and of its variation during metamorphism are essential to understand and model the exchange of reactive gases between the snowpack and the atmosphere. Therefore, the decay rate of SSA of five fresh snow samples was studied in the laboratory at –4, –10, and –15°C under isothermal conditions in closed systems. The time-evolution of the snow SSA can in all cases be very well described by an empirical law of the form, SSA = – A log(t + Δt) + B,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 26 publications
5
62
0
Order By: Relevance
“…Photomicrographs of snow crystals at various stages of evolution are shown in the Supporting Information. In contrast to isothermal metamorphism, where crystal shapes remain recognizable after weeks or even months (28), here the strong temperature gradient generates large water vapor fluxes that accelerate metamorphism. Changes in grain shapes are readily observable after a few hours.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Photomicrographs of snow crystals at various stages of evolution are shown in the Supporting Information. In contrast to isothermal metamorphism, where crystal shapes remain recognizable after weeks or even months (28), here the strong temperature gradient generates large water vapor fluxes that accelerate metamorphism. Changes in grain shapes are readily observable after a few hours.…”
Section: Resultsmentioning
confidence: 87%
“…As SSA decreases with snow aging (24,28,32,33), it decreased with depth inside the snowpack. Freshly fallen snow SSA values ranged from about 800 cm 2 g -1 for bullet rosettes and columns to 1171 cm 2 g -1 for very rimed dendritic snow.…”
Section: Resultsmentioning
confidence: 98%
“…Domine et al (2003) may have observed growth steps on surface hoar crystals studied by scanning electron microscopy (SEM), and whose height was about 1 µm, but it is not even totally certain that the structures observed were growth steps, and they did not seem to originate from a crystal edge, but rather from a grain boundary, so that the representativity of this observation may be limited. Indeed, the numerous SEM studies of snow crystals (Wergin et al, 1996;Domine et al, 2003;Erbe et al, 2003;Legagneux et al, 2003) usually do not show any structures that can be convincingly attributed to growth steps, which suggest that these could be undetectable by SEM and much smaller than 1 µm in most cases.…”
Section: Application To Snowpacks and Cloudsmentioning
confidence: 99%
“…While the formation of spherical and round bubbles was discussed theoretically and on experimental basis already three decades ago (List, 1958;Knight and Knight, 1968;List et al, 1972;Carras and Macklin, 1975;Macklin et al, 1976), little is known about the formation of non-spherical bubbles which must have a higher interface free energy than spherical bubbles. Their Y-shaped morphology is probably related to the void wedges at the triple junctions between frozen droplets retaining approximately their spheroid shape, and does not occur in a preferred orientation.…”
Section: Samples Of Natural Graupelsmentioning
confidence: 99%
“…Measured graupel densities vary, e.g. from 0.05 to 0.45 g cm −3 (Locatelli and Hobbs, 1974), 0.25 to 0.7 g cm −3 (Zikmunda and Vali, 1972), up to 0.5 to 0.7 g cm −3 (List, 1958). The densities of hailstones were found as low as 0.4 g cm −3 (Knight and Heymsfield, 1983), but generally lie around 0.8 g cm −3 (e.g.…”
Section: Introductionmentioning
confidence: 99%